2022
DOI: 10.1002/cam4.5351
|View full text |Cite
|
Sign up to set email alerts
|

Mobile application to support oncology patients during treatment on patient outcomes: Evidence from a randomized controlled trial

Abstract: Background: Cancer treatment requires substantial demands on patients and their caregivers. Mobile apps can provide support for self-management during oncology treatment, but few have been rigorously evaluated.Methods: A 3-month randomized controlled trial was conducted at a large cancer center to evaluate the efficacy of an app (LivingWith®) that provides selfmanagement support during cancer treatment on quality of life and health care utilization. Patients in chemotherapy treatment were randomized into the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Thirty‐six of 43 (84%) studies reported the proportion of participants who commenced the intervention out of the total number of eligible participants offered enrolment. The proportions were variable, ranging from 35 40 to 97% 41 for guided interventions with a mean of 68%, 36,37,40–52 and 20 50 ‐100% 51 for non‐guided interventions with a mean of 64% 7,34,38,39,53–69 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty‐six of 43 (84%) studies reported the proportion of participants who commenced the intervention out of the total number of eligible participants offered enrolment. The proportions were variable, ranging from 35 40 to 97% 41 for guided interventions with a mean of 68%, 36,37,40–52 and 20 50 ‐100% 51 for non‐guided interventions with a mean of 64% 7,34,38,39,53–69 …”
Section: Resultsmentioning
confidence: 99%
“…Ten studies evaluated the proportion of participants who used the intervention at least once, ranging from 85% 47 to 100% 37,70 for guided, and 52% 58 to 89.4% 56 for non-guided. Eleven studies collected data on the number of separate logins/visits by intervention group participants, with the average number being 9.5 37,70 for guided and 10.6 7,54,58,59,[62][63][64]67,71 for non-guided.…”
Section: Engagement: Intervention Usagementioning
confidence: 99%
See 1 more Smart Citation
“…For patients and healthcare professionals, the main clinical challenges are treatment adherence, symptom monitoring, symptom management, social support, and self-efficacy. Empowering oncology patients using digital technologies has been recognized as a promising strategy to improve therapy outcomes [98][99][100][101][102][103][104].…”
Section: Cancermentioning
confidence: 99%
“…First generation cancer drug-companion apps provide simple digital support to patients undergoing cancer treatment to enhance patient understanding and adherence. They have simple diary, tracking and communications functions 53 , 54 , 70 . Some of these apps use remote monitoring for dose adaptation to side effects, but, due to the increased HCP workload they create, and due to their lack of reimbursement, they have thus far only been used in clinical trials 71 – 73 .…”
Section: Introductionmentioning
confidence: 99%